Social Economy in Romania – from Concept to Practice - Petrescu, Claudia; Neguț, Adriana (Calitatea Vieții, 2018)
As a consequence of intensifying funding for social economy, the number of researches, publications and debates on social economy’s role and the awareness of the concept have increased. The main sources of funding have made an important contribution to how the social economy is understood and the development of this field in Romania. Based on the institutionalist theories according to which the development of the social economy and the organization and functioning of its entities depend on the economic, social and institutional context in which they operate (Kerlin, 2017; Rueshemeyer, 2009; Teasdale, 2012; Sepulveda, 2015), this article analyses the development of the social economy sector in Romania. The research question to which the article attempts to provide answers addresses the relationship between the definition of social economy and social enterprise and the subsequent development of these entities in Romania. Despite of intense efforts to define the social economy and legislation of the sector in recent years, the results of the research analysed in the paper indicate a lack of consistency, still present at national level, regarding the understanding of the social economy and social enterprises. Limiting the social economy sector especially to its role in social inclusion has led to its development especially in this area. Based on a background analysis of the data gathered in 2013 through a mix of qualitative and quantitative methods, the article presents an analysis of the degree of knowledge of the term, the defining characteristics of social enterprises and their main contributions, and, at the same time, draws attention on the tendency to underestimate the role of the social economy in social and economic development